Meningkatkan Hasil Belajar Siswa pada Materi Beriman kepada Rasul-Rasul Allah melalui Pembelajaran Problem Based Learning di Kelas IV SDN 32 Tanjung Beringin - Agustina, Ely (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to analyze the implementation of the Problem-Based Learning (PBL) model in improving the understanding of Islamic Religious Education (PAI) material, specifically the belief in the messengers of Allah, among students of SDN 32 Tanjung Beringin. The research was conducted over three cycles, involving group discussions, presentations, and evaluation of students’ learning outcomes. Based on the analysis of the first and second cycles, PBL showed a significant improvement in students’ understanding of the material and communication skills. In the third cycle, most students achieved excellent scores, with ten students earning an A grade, indicating that the PBL method is effective in enhancing students’ critical thinking and communication skills. The results of this study provide an insight that PBL encourages active participation, boosts self-confidence, and deepens students’ understanding of the topics being taught.